Essays in honor of M. Hashem Pesaran : panel modeling, micro applications, and econometric methodology - Chudik, Alexander; Hsiao, Cheng; Timmermann, Allan (Advances in econometrics ;, 2022)
The collection of chapters in Volume 43 Part B of Advances in Econometrics serves as a tribute to Professor M. Hashem Pesaran. Hashem is one of the most innovative, influential, and productive econometricians of his generation, with over 200 papers published in leading scientific journals to his credit along with highly influential books on both theoretical and applied topics, significantly pushing forward the frontiers of knowledge in econometrics and economics. Thanks to his profound and pioneering work on theoretical and empirical questions, the economics profession has gained a much better understanding of both the power and limitations of econometric analysis. Reflecting the diversity of Hashem's many contributions, this volume includes chapters on a wide variety of topics, including panel modelling, micro applications, and econometric methodology. The long list of topics includes studies analysing multiple treatment effects in panels, heterogeneity and aggregation, an exploration of the Orthogonal to Backwards Means (OBM) estimator, and an examination of potential reasons for anaemic productivity growth in Italy using recent dynamic heterogeneous panel data methods developed by Hashem Pesaran and his co-authors.